FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT INDIVIDU MELAKUKAN WHISTLEBLOWING: STUDI ANALISIS META - Fransiska Alicia (Fakultas Bisnis UKDW, 2021)
ABSTRACT This study aims to determine the factors that influence individual intention to do whistleblowing using 10 years of research data. The purpose of this research is to examine the association between Ethical Judgement Whistleblowing, Locus of Control, Organizational Commitment, Fraud Severity Rate, Personal Cost Reporting, Personal Responsibility Reporting, Job Satisfaction, Fair Treatment, Cooperativeness, Moral Reasoning, Anonym Reporting Channels, Education on Whistleblowing, Attitude, Perceived Behavioral Control, Organizational Support, Subjective Norms, Professional Commitment, Ethical Climate-Egoism, Ethical Climate-Benevolence, Ethical Climate-Principle, Anticipatory Socialization, Self-Interest, Feel Anger, Ethnic, Self-Efficacy, Managerial Status, Ethical Decision Making, Reward, Corporate Ethical, Gender, Controllability to whistleblowing intention. This research accumulates and integrates existing studies using meta-analysis techniques on 35 sample journals published between 2010-2020. Based on the research results, there are 28 variables as factors that can influence whistleblowing intention.Keywords: whistleblowing, whistleblowing intention, factors affecting whistleblowing, meta-analysis ABSTRAK Penelitian bertujuan untuk mengetahui faktor-faktor yang mempengaruhi niat individu melakukan whistleblowing dengan menggunakan 10 tahun data penelitian. Penelitian ini menguji pengaruh Ethical Judgement Whistleblowing, Locus of Control, Organizational Commitment, Fraud Severity Rate, Personal Cost Reporting, Personal Responsibility Reporting, Job Satisfaction, Fair Treatment, Cooperativeness, Moral Reasoning, Anonym Reporting Channels, Education on Whistleblowing, Attitude, Perceived Behavioral Control, Organizational Support, Subjective Norms, Professional Commitment, Ethical Climate-Egoism, Ethical Climate-Benevolence, Ethical Climate-Principle, Sosialisasi Antisipatif, Self-Interest, Feel Anger, Suku Bangsa, Self-Efficacy, Managerial Status, Ethical Decision Making, Reward, Corporate Ethical, Jenis Kelamin, Controllability terhadap niat whistleblowing. Penelitian ini mengakumulasi dan mengintegrasikan studi yang telah ada dengan menggunakan teknik meta analisis terhadap 35 jurnal sampel yang dipublikasikan antara tahun 2010-2020. Berdasarkan hasil penelitian, terdapat 28 variabel sebagai faktor yang dapat mempengaruhi niat whistleblowing.Kata kunci: pengaduan, niat pengaduan, faktor yang mempengaruhi pengaduan, meta analisis